Blue cures blue but be cautious - Pranav Sikka; V K Bindra; Seema Kapoor; Vivek Jain; K K Saxena (Wolters Kluwer Medknow Publications, 2011)
Methemoglobinemia is a disorder characterized by the presence of >1% methemoglobin (metHb) in the blood. Spontaneous formation of methemoglobin is normally counteracted by protective enzyme systems, for example, nicotinamide adenine dinucleotide phosphate (NADPH) methemoglobin reductase. Methemoglobinemia is treated with supplemental oxygen and methylene blue (1-2 mg/kg) administered slow intravenously, which acts by providing an artificial electron acceptor for NADPH methemoglobin reductase. But known or suspected glucose-6-phosphate dehydrogenase (G6PD) deficiency is a relative contraindication to the use of methylene blue because G6PD is the key enzyme in the formation of NADPH through pentose phosphate pathway and G6PD-deficient individuals generate insufficient NADPH to efficiently reduce methylene blue to leukomethylene blue, which is necessary for the activation of the NADPH-dependent methemoglobin reductase system. So, we should be careful using methylene blue in methemoglobinemia patient before G6PD levels.